SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/135469-ms
|View full text |Cite
|
Sign up to set email alerts
|

Making High Quality Frac Water out of Oilfield Waste

Abstract: Fresh water and affordable energy are two of the most valuable resources on the planet for sustaining economic growth and development. As the demand for oil and gas continues to increase, the fresh water consumption rate by exploration and production (E&P) activities is skyrocketing. Competition for fresh water is threatening to become an industry-limiting factor in some oil and gas plays. To ensure that the fresh water needed by the oil and gas industry is available in the future, better water resource manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 4 publications
2
29
0
Order By: Relevance
“…Thermally-regenerated FO has also been modeled by Semiat et al [17]. An FO pilot system with RO regeneration (FO-RO) was used to concentrate low-salinity O&G wastewater [2,18]. FO-RO has also been suggested to be more efficient than RO for seawater desalination [19,20], but other studies have shown that this is unlikely [21,22].…”
Section: Assessment Of Technologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Thermally-regenerated FO has also been modeled by Semiat et al [17]. An FO pilot system with RO regeneration (FO-RO) was used to concentrate low-salinity O&G wastewater [2,18]. FO-RO has also been suggested to be more efficient than RO for seawater desalination [19,20], but other studies have shown that this is unlikely [21,22].…”
Section: Assessment Of Technologiesmentioning
confidence: 99%
“…FO-RO has also been suggested to be more efficient than RO for seawater desalination [19,20], but other studies have shown that this is unlikely [21,22]. Another FO pilot plant forgoes draw regeneration in favor of "osmotic dilution" [2,18]: the dilution of a pure sodium chloride solution powers the concentration of O&G wastewater. Osmotic dilution is also used in emergency hydration [23], fertigation [24], and other applications described in [25].…”
Section: Assessment Of Technologiesmentioning
confidence: 99%
See 3 more Smart Citations